PENILAIAN QUALITY CONTROL TERHADAP PRODUK KERJA SISWA PRAKERIN DI TEACHING FACTORY SMK - Muhamad Agus Sriyono; Muhammad Sayuti; Muhammad Kunta Biddinika; Hasnul Azwan (Jurnal Taman Vokasi, 2025)
The purpose of the study was to; (1) analyze the quality control assessment of the results of the Prakerin students' products at TEFA vocational high school, (2) analyze efforts to improve the entrepreneurial spirit of Prakerin students at TEFA vocational high school, (3) analyze how to improve the activeness of Prakerin students at teaching factory SMK and (4) provide suggestions and input to quality control so that the quality of Prakerin students' products at teaching factory SMK is in accordance with consumer orders. Qualitative research method with a case study approach, Data collection using semi-structured interviews with respondents Principal, quality control staff, teaching factory managers, teachers and Prakerin students at the teaching factory, with the aim of obtaining appropriate and accurate data. Research results; (1) the quality of te products of teaching factory internship students must be in accordance with standards, so strategies are needed; (a) preparation of student competencies, (b). planning, implementation of learning, production activities, and industrial cooperation, (c) students are required to be honest, disciplined, responsible and active, and (d) determining standard operating procedures. (2) students' entrepreneurial spirit is influential during internship at teaching factory. Entrepreneurial spirit includes the ability to think creatively, innovatively, dare to take risks, and take advantage of business opportunities. Internship at teaching factory is a place to produce young entrepreneurs, create jobs and produce graduates with technical skills. (3) efforts to improve the activeness of Internship students (4) suggestions and input from quality control.